COVID‐19 in the Clinic: Aerosol Containment Mask for Endoscopic Otolaryngologic Clinic Procedures. (22nd June 2021) - Ference, Elisabeth H.; Kim, Wihan; Oghalai, John S.; Kim, Jee‐Hong; Applegate, Brian E.
Abstract : Objective: To create an aerosol containment mask (ACM) that contains aerosols during common otolaryngologic endoscopic procedures while protecting patients from environmental aerosols. Study Design: Bench testing. Setting: Mannequin testing. Methods: The mask was designed in SolidWorks and 3‐dimensional printed. Mannequins were fitted with a nebulizer to generate aerosols. Commercial particle counters were used to measure mask performance. Results: The ACM has 2 ports on either side for instruments and endoscopes, a port for a filter, and a port that can evacuate aerosols contained within the mask via a standard suction pump. The mask contained aerosols on a mannequin with and without facial hair when the suction was set to 18.5 L/min. Other types of masks demonstrated substantial aerosol leakage under similar conditions. In a subsequent experiment, the ACM contained aerosols generated by a nebulizer up to the saturation of the particle detector without measurable leakage with or without suction. Conclusion: The ACM will accommodate rigid and flexible endoscopes plus instruments and prevent leakage of patient‐generated aerosols, thus avoiding contamination of the room and protecting health care workers from airborne contagions. Level of evidence: 2.